Performance of parental genotypes and inheritance of Angular Leaf Spot Phaeosariopsis griseola) resistance in the common bean (Phaseolus vulgaris) - Chataika, Bartholomew Y.E.; Bokosi, J.M.; Kwapata, MB; Chirwa, Rowland; Mwale, VM; Mnyenyembe, P; Myers, JR (2010)
Two studies, one on performance of six common bean parental genotypes and another on inheritance of resistance to Phaeosariopsis griseola (Pg) in the common bean were carried out in Malawi. Common bean entries namely; Chimbamba, Nasaka, RC 15, CAL 143 and Mexico 54 were evaluated on station in the 2004/2005 growing season at Bunda, Dedza, Ng'onga and Ntchenachena sites. The second study started by generating F1s and then F2 and F3 seeds in greenhouse at Bunda College. CAL 143 and Mexico 54 were sources of Pg resistance genes while Chimbamba, Nasaka and RC 15 were susceptible recipient parents. Following green house trials, Pg resistance was evaluated on station in the same sites. CAL 143 was highest yielding but unstable across sites. RC 15 was stable and gave the highest yield at the dry-spell-stricken Ng onga whereas Mexico 54 was superior at Ntchenachena but highly unstable across sites. Yield was strongly correlated to number of effective pods per plant in all genotypes. The inheritance study showed that resistance to Pg in the common bean is controlled by one gene using both CAL 143 and Mexico 54 as resistant parents.